Mystique et révolution : Rosa L. d’Alfred Döblin - Alfred Prédhumeau (Recherches Germaniques)
The aim of the article is to present the mystical parts in the Rosa Luxemburg-novel in Döblin’s November 1918. We approach the three main functions of this mysticism in the areas of love, religion, and politics. We try to show that satanic mysticism is a key factor in the author’s attempt to explain the tragic end of his protagonist, as well as the failure of the January uprising in Berlin in 1919.